La ilustración como discurso visual en la representación de el personaje el comerciante de Saquisilí. - Venegas Báez, Alejandra Verónica (2023)
Saquisilí is a small town located in the province of Cotopaxi, recognized as the main commercial transport route in the country due to its ability to connect the Highland and the Coastal regions. In the 1930s, Saquesilense merchants were considered people of high social rank for transporting inter-Andean products, traveling extensive routes to make their sales. These experiences are often recounted by older adults who manage to fondly remember their ancestors. At the moment, Saquisilense population is unaware of the history of the routes and adversities of this activity and the current impact of trade, since it is one of the central activities of the town. For this reason, the elaboration of an illustrated book is proposed through the Design Sprint methodology where the adversities experienced by the merchants of the early 20th century are compiled and depicted, based on the use of the graphic style exposed in old illustrations created by the residents. It started from a script based on bibliographic and documentary data, as well as interviews with relatives and successors of this traditional trade. Finally, the visual discourse disseminates the character of the merchant through illustrations that encourage visual memory and safeguard the experiences of the ancestors. Just as the importance of the origin of trade in the central Highlands of Ecuadoris given.